Resolução de problemas e modelagem matemática: Uma experiência na formação inicial de professores de Física e Matemática - Domingos, Ronero Marcio Cordeiro (2016)
The aim of this study was to identify and understand how undergraduated students of Physics and Mathematics develop their skills and attitudes to classroom practice in the context of mathematical modeling using the mathematics teaching-learning methodology through solving problems. For this research, it was employed as a scientific methodology, the Model Thomas A. Romberg, where he presents ten key activities for the development of a scientific research. From this model, it was possible to carry out the research, planning and todevelop this work. The field research was carried out with students of Physics and Mathematics major of the Federal Institute of Sertão Pernambucano, campus of Salgueiro / PE, and the Faculty of Humanities of the Sertão Central - FACHUSC. For these students it was offered an extension course on Ordinary Differential Equations in the context of Mathematical Modeling. The data collection was done through questionnaires, notebooks and students’nots, and especially by recordings made during each meeting. Da analysis of the data collected during the field research, it was found that the methodology Problems Solving, worked in the context of Mathematical Modeling, is a promising way to prepare future teachers of physics and mathematics to develop skills and attitudes to the classroom practice. The work in the field of research given to prospective teachers moments of creativity, interest in the contents worked and active participation in the activities developed during the course of extension.